A Design and Development of Online Ticket Reservation System - Niranjan R. Chougala; Malatesh S.H.; Manjula R. Chougala; Shruthi S.; Shridhar V.; Surendra Babu M.S. (International Journal of Computer Science Languages, 2024)
The purpose of this case study is to develop and demonstrate various facilities and features available in Full Stack Development using Django by considering a simple example of an Online Ticket Reservation System (OTRS). The concepts of Django Models, Views, Templates, Admin Interfaces, and Forms are used to ensure this case study utilizes all features of the framework to make it the complete miniature product. In addition, a well-documented report and simple explanation related to the product are incorporated to complete the software development product cycle. For a better understanding of the product and its use, the simple business logic has been developed and documented so that the user can easily improve and scale up accordingly. Various interactions and interfaces among the code have been shown to make naive users or developers understand better as well as encourage contributing additional business logic easily. Results from executing the code have been shown with a brief explanation. This work targets and encourages naïve developers to understand the full stack development framework better by considering a simple case study.
Keywords: Django Models; Full stack development; admin interfaces; forms; templates; views